Pengaruh Faktor Psikologis Terhadap Pengambilan Keputusan Wisatawan dalam Mengunjungi Taman Bunga Nusantara Kabupaten Cianjur - Rosiana, Eka Nuraisah; Hainim, Bem; Sadkar, Upiek Haeryah (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2018)
Psychological factors are factors inherent in the individual, which will affect how the various kinds of stimuli given by marketers, will affect consumer recognition of the needs, information seeking, and a variety of alternatives before deciding to make a visit or not. This research, entitled "The Influence of Psychological Factors on Tourist Decision to Visit Taman Bunga Nusantara Cianjur Regency" conducted in order to determine the psychological factors of tourist and the decision-making of tourist in visiting Taman Bunga Nusantara Cianjur Regency, as well as to analyze the influence of psychological factors towards tourist decision making to visit Taman Bunga Nusantara Cianjur Regency. The used method is accidental sampling. Respondents in this research were the visitors of Taman Bunga Nusantara as the location of the research, a total of 120 respondents. Based on the analysis, the firmest aspect of psychological factors is personality. As well as tourist decision in visiting Taman Bunga Nusantara was in the low category. Simultaneously, psychological factors significantly influence tourist decision in visiting Taman Bunga Nusantara Cianjur Regency. Based on the research results, the manager of the Taman Bunga Nusantara in order to create a marketing strategy that can affect consumers by providing a strong stimulus to be remembered very well by travelers.